The importance of deep genotyping in crop breeding - Zambelli, Andres Daniel (2023)
One of the greatest challenges facing humanity is the development of sustainable strategiesto ensure food availability in response to population growth and climate change. Oneapproach that can contribute to increase food security is to close yield gaps and enhancinggenetic gain; to such end, what is known as “molecular breeding” plays a fundamental role.Since a crop breeding program is mainly based on the quality of the germplasm, its detailedgenetic characterization is mandatory to ensure the efficient use of genetic resourcesand accelerating development of superior varieties. Deep genotyping is an essential toolfor a comprehensive characterization of the germplasm of interest and, fortunately, thetechnology is now accessible at a reasonable cost. What must be ensured is the correctinterpretation of the genotypic information and on that basis develop efficient practicalmolecular crop breeding strategies that respond to the real needs of the breeding program.